(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
An attempt to distinguish the primary migration determinants in the West Pomera-nian Province, in Commune cross section approach, during 2001, 2007 and 2008, was madein this paper. To achieve this, regression equations were constructed in which the quotient of migration inflows and outflows was applied as the dependent variable. Based on the accomplished econometric analysis it’s been demonstrated that the main determinant of permanent migrations associated with crossing the Commune border during the surveyed years was the aspiration to improve housing conditions. An impor-tant role was also played by the levels of Community unemployment and affluence. However, significance of those of factors varied in time.